Alterations of the Murine Gut Microbiome with Age and Allergic Airway Disease - Marius Vital; Jack R. Harkema; Mike Rizzo; James Tiedje; Christina Brandenberger (Journal of Immunology Research)
The gut microbiota plays an important role in the development of asthma. With advanced age the microbiome and the immune system are changing and, currently, little is known about how these two factors contribute to the development of allergic asthma in the elderly. In this study we investigated the associations between the intestinal microbiome and allergic airway disease in young and old mice that were sensitized and challenged with house dust mite (HDM). After challenge, the animals were sacrificed, blood serum was collected for cytokine analysis, and the lungs were processed for histopathology. Fecal pellets were excised from the colon and subjected to 16S rRNA analysis. The microbial community structure changed with age and allergy development, where alterations in fecal communities from young to old mice resembled those after HDM challenge. Allergic mice had induced serum levels of IL-17A and old mice developed a greater allergic airway response compared to young mice. This study demonstrates that the intestinal bacterial community structure differs with age, possibly contributing to the exaggerated pulmonary inflammatory response in old mice. Furthermore, our results show that the composition of the gut microbiota changes with pulmonary allergy, indicating bidirectional gut-lung communications.